Status Report of the Work of the IMF and the World Bank on the Twelve-Month Pilot Program on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) Assessments and Delivery of AML/CFT Technical Assistance. (Policy Papers; Policy Paper ;, 2003)
NULL.